Classroom Environment Engraving Teachers’/students’ Level of Motivation - Rajbhandari, Mani Man Singh (SXC Journal, 2024)
Classroom environment plays a pivotal role in increasing or decreasing the level of motivation of both the teachers and students. Classroom environment could involve various elements, from behaviors and personality to resource availability. This study explores to understand who develops the classroom environment. For this study, a qualitative design was applied. Open-ended interview techniques were conducted. Open interview questions were distributed to teachers and students of various departments, of both bachelor’s and master’s degrees. Altogether 18 respondents participated in this study and shared their opinion on classroom environment and their level of motivation. Coded data was triangulated for analysis, and the crystallization method was applied for giving additional meaning to the analyzed data. The results suggest that classroom environment is shaped by both students and teachers’ behaviour. It was found that teachers and students’ views mostly contributed to the classroom environment and the level of motivation to learn and to teach. Teachers with a flexible nature can complement in motivating students in creating a harmonious classroom environment. Within the same classroom, there could be multiple environments at different times with different teachers but with the same group of students. Even within the same student group, there exist various natures – some find humor interesting, for others interaction and discussion make them active. Students are vigilant and are concerned about the teaching methodology. This can raise the level of motivation of students, which can have a positive impact on the teachers. Teachers’ motivation level increases when the classroom environment is organized and disciplined as expected by them. The changes and the new generation create a different environment. This instigate a teacher to also change their ways of teaching that is situationally-fit. This generates difficulties for a teacher because it instigate them to change their teaching pattern, behavior and personality. Teachers’ level of motivation and classroom environment have a close relation. Both contribute to the quality of education.